2022
DOI: 10.1002/pmic.202200124
|View full text |Cite
|
Sign up to set email alerts
|

Integrated proteome and acetylome analyses unveil protein features of gestational diabetes mellitus and preeclampsia

Abstract: Gestational diabetes mellitus (GDM) and preeclampsia (PE) are associated with maternal and infant health. Although the pathogenesis of PE and GDM remains controversial, oxidative stress is involved in the underlying pathology of GDM and PE. Protein lysine acetylation (Kac) plays an important regulatory role in biological processes. There is little data regarding the association of the maternal acetylome with GDM and PE. This study aimed to assess the potential value of the proteome and acetylome for GDM and PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…This dissimilarity may be due to variations among the individual samples and differences between the human and murine specimens. In a similar vein, Hu et al 21 also reported an upregulation of cell oxidant detoxification mechanisms in GDM placentas, which aligns with our findings. Additionally, Assi's research 22 indicated alterations in the enrichment of pathways related to oxidative stress, metabolic processes, and complement and coagulation cascades, further supporting our observations.…”
Section: Alterations Of the Landscape Of Proteins In Gdm Placentasupporting
confidence: 93%
“…This dissimilarity may be due to variations among the individual samples and differences between the human and murine specimens. In a similar vein, Hu et al 21 also reported an upregulation of cell oxidant detoxification mechanisms in GDM placentas, which aligns with our findings. Additionally, Assi's research 22 indicated alterations in the enrichment of pathways related to oxidative stress, metabolic processes, and complement and coagulation cascades, further supporting our observations.…”
Section: Alterations Of the Landscape Of Proteins In Gdm Placentasupporting
confidence: 93%
“…GDM is associated with long-lasting complications in the short and long term, such as macrosomia ( Song et al, 2022 ), dystocia ( Crowther et al, 2022 ), childhood obesity in the child ( Choi et al, 2022 ), recurrence of GDM ( Giuliani et al, 2022 ), developing type 2 diabetes ( Vounzoulaki et al, 2020 ) and cardiovascular disease in the mother ( Christensen et al, 2022 ). Emerging evidence suggests ferroptosis contributes to the pathogenesis of GDM ( Han et al, 2020 ; Gautam et al, 2021 ; Zhang et al, 2022c ; Hu et al, 2022 ; Zaugg et al, 2022 ). The insulin sensitivity shifts depending on the requirements of pregnancy, which is an important metabolic adaptation during healthy pregnancy ( Di Cianni et al, 2003 ).…”
Section: Role Of Ferroptosis In Pregnancy Related Diseasesmentioning
confidence: 99%